Variation in physico-chemical characteristics of pea (Pisum sativum) grown under rainfed condition - EREIFEJ, K I; AL-KARAKI, G N; SHIBLI, R A; EL-SHATNAWI, M K (The Indian Journal of Agricultural Sciences, 2013)
Twelve exotic lines and a local variety pea [ Pisum sativum (L.) var arvense Poir,] were grown in randomized complete block design at Maru in north Jordan during 1993-94 growing season. The seeds were studied for their physical properties, chemical composition, mineral analysis and cooking characteristics. Significant variation was noticed in physical properties. ’Local Sel 1690’ recorded the highest fat contentÂ Â (1.3%). Strong positive correlation was found between water absorption and ash content (r = 0.68), fat % (r = 0.55), K%Â (1’.= 0.82) and Mg% (r=0.78), but the lines having high carbohydrate content showed low protein content (r = -D.89). The mineral contents were comparable among the lines studied. The increase (%) in cooked weight was 195% (’MG 102029’)-271.7% (local variety). The increased volume of the cooked pea was 215% (’MG 102029’)-280% (’Local Sel 1690’). The cooking time for all the lines was 40-60 min.